2007
DOI: 10.1007/s10608-007-9132-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Changes in Obsessive Compulsive Symptoms Over a Six-Month Follow-Up: A Prospective Test of Cognitive Models of Obsessive Compulsive Disorder

Abstract: Cognitive models of obsessive compulsive disorder (OCD) propose that OCD-related beliefs (e.g., inflated responsibility) and negative life events should predict changes in OC symptoms over time (The science and practice of cognitive behavior therapy. Oxford: Oxford University Press). However, very little research has tested these longitudinal predictions. The current study sought to replicate and extend findings by Coles and Horng (2006, Cognitive Therapy and Research, 30, 723-746) showing that OCD-related b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 82 publications
4
21
0
1
Order By: Relevance
“…Prior prospective research by Coles and Horng (2006) demonstrated that obsessive beliefs are more predictive of some OCD symptoms (e.g., obsessing) than others (e.g., hoarding) over a 6-week period. A similar investigation by Coles et al (2008) found that obsessive beliefs predicted changes in the distress associated with OC symptoms (despite much additional variance to be accounted for), but not their frequency. One limitation of this prospective research examining the association between obsessive beliefs and OCD is the absence of an identifiable stressor that has been implicated in the etiology of OCD symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…Prior prospective research by Coles and Horng (2006) demonstrated that obsessive beliefs are more predictive of some OCD symptoms (e.g., obsessing) than others (e.g., hoarding) over a 6-week period. A similar investigation by Coles et al (2008) found that obsessive beliefs predicted changes in the distress associated with OC symptoms (despite much additional variance to be accounted for), but not their frequency. One limitation of this prospective research examining the association between obsessive beliefs and OCD is the absence of an identifiable stressor that has been implicated in the etiology of OCD symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…We chose an undergraduate nonclinical sample for this aim to provide a wide range of scores on measures of OCD symptoms (Coles et al, 2008;OCCWG, 2005), given theoretical assumptions that OC phenomena lie on a continuum from normality to psychopathology (e.g., Burns, Formea, Keortge, & Sternberger, 1995;Sternberger & Burns, 1990). Moreover, previous research has demonstrated the utility of student samples in advancing theories of OCD (see Gibbs, 1996, for a review).…”
Section: The Current Studymentioning
confidence: 99%
“…One longitudinal study indicated that parents' tendency to negatively interpret intrusive infant-related thoughts early in the postpartum period mediated the relationship between pre-childbirth OC beliefs and late postpartum OC symptoms (Abramowitz, Nelson, Rygwall & Khandker, 2007). However, a recent 6-month longitudinal study found that OC-beliefs were of only modest value in predicting OC symptoms variation among college students (Coles, Pietrefesa, Schofield, & Cook, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to Christensen et al (1999), cognitive biases are considered important in the development and maintenance of several mental disorders and may have implications for specific disabilities in medical populations. Further, recent research has shown that a wide range of life stressors increase obsessional and compulsive behavior in a non-clinical sample (Coles, Pietrefesa, Schofield, & Cook, 2008). This makes a general medical sample a highly desirable comparison group to individuals with OCD as it would be expected that there would be elevated scores on several indices of cognitive biases associated with OCD such as concerns over contamination or perfectionism, but that these biases should not be as high as found in individuals with OCD.…”
Section: Introductionmentioning
confidence: 99%